Keterampilan Menulis Teks Cerpen Siswa Kelas XI MAN Kota Makassar di Masa Pandemi Covid-19 - Mei Wahyuni; Muhammad Saleh; Idawati Idawati (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract: This study is a study that aims to examine students' skills in writing short stories during the Covid-19 pandemic. The skills of writing short stories written by students of class XI MAN 1 Makassar City can be seen from the results of the writings written by students. Students' short story writing skills can be seen based on two aspects, namely the structure and linguistic characteristics of the short story text. The population in this study was 40 students, while the samples in this study were students of class XI MAN 1 Makassar City, which consisted of 20 students of class XI MIA 5 and 20 students of class XI IIS 1. Based on the results of research that has been done , obtained an assessment in terms of the structure of the short story text, namely, abstract, orientation, complication, evaluation, resolution, and code, the overall score obtained is 69.68. The average value obtained by students based on the linguistic characteristics of the short story text is given an assessment according to the writing of the short story text, namely vocabulary, language style, descriptive sentences, non-standard and informal language, the average value obtained by students is 71.40. It was concluded that the overall score was based on the assessment category in accordance with the score assessment in this study, namely from the highly skilled category of class XI students of MAN 1 Makassar City, the score was 39.37%. The assessment of the skilled category in class XI students the overall score is 98.75%, this assessment is obtained by students based on the structure and linguistic characteristics of the short story text of class XI students of MAN 1 Makassar City and is included in the category of skilled in writing short stories. Based on the fairly skilled category, the overall score obtained by students is 76.87%. Writing short stories based on the category of less skilled assessment, the value obtained by students in writing short stories is 350%. Overall, based on the assessment category for writing short stories, the grades obtained by class XI MAN 1 Makassar City students were categorized as skilled in writing short stories during the Covid-19 pandemic